Peran Manajemen Resiko dalam Meningkatkan Ketahanan Bank Syariah di Era Digital - Bekti Widyaningsih; Ashlihah; Tolib Ibnu Afan (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
In the ever-evolving digital era, Islamic banks face new challenges in delivering safe and reliable banking services. In this context, risk management has an important role in ensuring the reliability of Islamic banks in the digital era. This study aims to analyze the role of risk management in improving the reliability of Islamic banks in the digital era. The research method used is a descriptive-analytical approach by collecting data through literature study and analysis of relevant literature. This research highlights several important aspects in the role of risk management in the context of Islamic banks in the digital era, including risk identification, risk evaluation, risk control, and risk monitoring. In conclusion, risk management has a crucial role in enhancing the reliability of Islamic banks in the digital era. By adopting a comprehensive approach in identifying, evaluating, controlling, and monitoring risks, Islamic banks can maintain the integrity of the Islamic banking system and build customer confidence in the use of digital banking services. These efforts will help Islamic banks to remain relevant and competitive in the face of the evolving challenges of the digital era.